2017
DOI: 10.1111/pai.12768
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to dust mite defines different phenotypes of asthma: A multicenter study

Abstract: Similar asthma phenotypes may occur in children despite differences in their atopic state. In atopic children, sensitizing allergens in the indoor environment may increase airway inflammation worsening pulmonary function. Moreover, environmental exposures may contribute to the development of asthma-like symptoms also in the absence of atopic sensitization, thus contributing to asthma overdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Silvia de Magalhaes Simoes and co-authors showed that 143 (36 %) children of 397 children with bronchial asthma had intermittent course; 160 (40 %) -mild persistent course; 51 (12.8 %) -persistent moderate course and 43 (10.8%) -persistent severe course of the disease [17]. In the same way as in our study the prevalence of allergic rhinitis in children living in Korea or in the Southern Mediterranean region was associated with their place of residence and Dermatophagoides pteronyssinus was the dominant in allergen-induced bronchial asthma [18,19]. The incidence of bronchial asthma and hypersensitivity to domestic allergens was recorded at 12 % vs. 3 % and 56 % vs. 38 % in Lima as compared with Tumbes, and the risk factor for allergic rhinitis development was also the sensitization to domestic allergens [20].…”
Section: Resultssupporting
confidence: 77%
“…Silvia de Magalhaes Simoes and co-authors showed that 143 (36 %) children of 397 children with bronchial asthma had intermittent course; 160 (40 %) -mild persistent course; 51 (12.8 %) -persistent moderate course and 43 (10.8%) -persistent severe course of the disease [17]. In the same way as in our study the prevalence of allergic rhinitis in children living in Korea or in the Southern Mediterranean region was associated with their place of residence and Dermatophagoides pteronyssinus was the dominant in allergen-induced bronchial asthma [18,19]. The incidence of bronchial asthma and hypersensitivity to domestic allergens was recorded at 12 % vs. 3 % and 56 % vs. 38 % in Lima as compared with Tumbes, and the risk factor for allergic rhinitis development was also the sensitization to domestic allergens [20].…”
Section: Resultssupporting
confidence: 77%
“…were found in house dust samples. 54 that school endotoxin levels were positively associated with non-atopic asthma, which suggested exposure at school can contribute considerably to the overall environmental exposure of children to endotoxin. We hypothesize in this study school hygiene procedures were not adequate in effectively removing indoor endotoxin contamination.…”
Section: Indoor Der P 1 and Endotoxinmentioning
confidence: 93%
“…Increased sensitization rates to house dust mites, molds, and allergens from furry animals 55,56 2. More severe phenotypes of allergic rhinitis and asthma, as compared to those induced by outdoor allergens [58][59][60] During childhood Higher bronchial inflammation and reduced lung function in sensitized children with wheezing episodes 57 Colonization of the households by molds and cockroaches due to dampness 75 Other large studies have also reported similar links between outdoor pollution and childhood asthma. 76,77 The ESCAPE project also analyzed five European adult cohorts (overall ~7500 participants) and found that higher exposure to nitrogen monoxide (NO), NO 2 , and PM 10 from traffic was associated with decreased lung function during adulthood.…”
Section: Environmental Factors Health Outcomesmentioning
confidence: 94%
“…Moreover, HDM are the most common triggers of airway allergy, as up to 50% of asthmatics are sensitized to them . Recent data suggest that in children with wheezing episodes, sensitization to HDM is associated with greater bronchial inflammation and reduced lung function . Importantly, indoor allergens induce more severe phenotypes of airway allergy than outdoor seasonal allergens .…”
Section: Indoor Air Pollutionmentioning
confidence: 99%